Market Dynamics: the Impact of Modern Mini Markets on the Existence of Traditional Shops and Markets in Bantul District - Budiman, Nikko; Suryono, Leli Joko; Prasetyoningsih, Nanik (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This research discusses the impact of modern minimarkets on traditional shops and markets in Bantul Regency. Traditional markets in Indonesia face quite big challenges due to the emergence of minimarkets, which offer various advantages such as strategic locations, parking facilities, affordable prices, and better service. This research uses a juridical method with secondary data analysis and interviews with related parties. The research results show that modern minimarkets significantly reduce the turnover and number of customers of traditional retail stores. Government policies regulating the distance and zoning of minimarkets, as regulated in Bantul Regent Regulation Number 12 of 2010, have yet to be fully effective in protecting the existence of traditional markets. This study recommends policy revisions and capital and training support for conventional shop owners to create fairer and more sustainable business competition. Collaborative efforts between the government and business actors are needed to maintain the balance of the retail ecosystem and support local economic growth.